2010
DOI: 10.1111/j.1464-5491.2010.03001.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of postpartum glucose tolerance testing after pregnancies complicated by gestational diabetes

Abstract: Aims To review postpartum glucose tolerance in women with gestational diabetes and evaluate the role of formal 75 g oral glucose tolerance testing vs. fasting plasma glucose in screening for persistent abnormalities.Methods Retrospective study of 985 pregnancies over a 10 year period in a mixed ethnic cohort of women who underwent follow-up glucose tolerance testing at 6 weeks postpartum. Diagnosis obtained by oral glucose tolerance test was tested against that from the fasting plasma glucose value.Results The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 18 publications
3
24
1
Order By: Relevance
“…These results are similar to recent data from McClean et al (6), who found that an FPG cut off value of R6.1 mmol/l identified abnormal glucose tolerance in 199 of the 272 cases (sensitivity 0.73). Interestingly, of these 272 women, 109 had frank diabetes, of whom 11 (10%) had an FPG %6.0 mmol/l.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are similar to recent data from McClean et al (6), who found that an FPG cut off value of R6.1 mmol/l identified abnormal glucose tolerance in 199 of the 272 cases (sensitivity 0.73). Interestingly, of these 272 women, 109 had frank diabetes, of whom 11 (10%) had an FPG %6.0 mmol/l.…”
Section: Discussionsupporting
confidence: 82%
“…Reported prevalence of pre-diabetes and T2DM following GDM ranges from 7 to 35% (4). The current literature suggests that the rate of uptake of post partum diabetes screening is low, and that a fasting plasma glucose (FPG) alone may miss up to 72% of cases of post partum dysglycemia (5,6). To date studies on persistent post partum hyperglycemia have shown inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to the OGTT, single glucose and haemoglobin A1c levels have consistently been shown to be insensitive screening tests for type 2 diabetes in the postpartum period. [25][26][27][28][29][30][31][32][33] Recently, Capula et al found that 32.3% of women with previous GDM completed an OGTT within 6 and 12 weeks postpartum. Prepartum counselling and a diagnosis of polycystic ovarian syndrome were the strongest predictors of adherence to completing a postpartum OGTT.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study does not report the sensitivity and specificity of fasting plasma glucose in identifying impaired glucose tolerance. Mc Lean et al showed that 18 a postpartum fasting plasma glucose measurement alone is not sensitive enough to classify glucose tolerance status accurately. Our survey showed 82% of units offered OGTT at six weeks postnatal period.…”
Section: Discussionmentioning
confidence: 99%